Event management knowledge domains as the antecedents for successful cultural events in Malaysia / Qistina Donna Lee Abdullah - Lee Abdullah, Qistina Donna (2014)
Event management is currently becoming a blooming industry in the world. It has been recognized as a new dimension in business network for funds exchange and capital income apart from generating vast career opportunity in the market. The revenue collected from events are various according to its category such as events in the tourism industry, destination attractions, cultural and festivals, MIC industry, national and international events. In Malaysia, cultural events and festival have be converted into a prospect developing area for government, agencies and private sectors to engage. Apart from formulate earnings, this sector also help to secure and preserve the authenticity of Malaysian arts, cultural and heritage. Acknowledge the significant of event management existence, therefore this study is establish to investigate the practice of event management knowledge domains as the antecedents for successful cultural events in Malaysia. The objectives of this research is to identify current management strategies used in conducting cultural events in ten government cultural agencies, fourteen government state offices under MICC and forty one SMEs event management companies nationwide, to determine the relationship between dimensions of event management domains and event success factors and to verify the moderating influence of expert event manager on the relationship between event management knowledge domains and event success. This exploratory study employed quantitative survey with structured questionnaire in an effort to examine the theory and acquire new knowledge by utilizing the statistical methods to validate results. This study generally has successfully answered all the three (3) research objectives, and three (3) research questions. Several hypotheses were supported and others were not indicating that three (3) EMBOK domains (Functional Administration, Operation Network and Organizational Resources) are significant to influence the event success on Return on Objectives, meanwhile all four (4) EMBOK domains (Functional Administration, Operation Network, Risk Management, and Organizational Resources) are significantly influence the event success in terms of Event Recognition. On the other hand, it also proven that the employment of expert event manager moderates the relationship between three (3) EMBOK domains (Functional Administration, Operation Network and Organizational Resources) and the event success in terms Event recognition. The findings erve as supplement to the existing Event Management Body of Knowledge with the additional new sphere of expert event manager in the framework.